Nutritious underutilized species - Fonio - Alercia, A.; Bioversity International (2013)
Fonio is a highly palatable cereal that is drought tolerant. It is often consumed in West Africa before most crops are ready to harvest because it is one of the world’s fastest maturing cereals. It is believed to be one of the oldest cereals in West Africa, where it is indigenous.Fonio is a neglected and underutilized species (NUS): a category of non-commodity cultivated and wild species, which are part of a large agricultural biodiversity portfolio today falling into disuse for a variety of agronomic, genetic, economic, social and cultural factors. NUS are traditionally grown by farmers in their centres of diversity, where they support nutrition security and other livelihood goals of local communities while contributing to meet their socio-cultural needs and traditional uses. Until recently these species have been largely ignored by research and development, becoming less competitive than well established major crops and losing gradually their diversity and associated traditional knowledge.